A Kalman filter approach to Fisher effect: Evidence from Nigeria - Omorogbe J. Asemota; Dahiru A. Bala (CBN Journal of Applied Statistics, 2011)
This paper investigates evidence of a Fisher effect in Nigeria by employing quarterly CPI inflation and Nominal interest rates data. For a more robust result we conducted integration and cointegration tests in order to examine time-series properties of the variables. Using Co-integration and Kalman filter methodologies, the study did not find evidence of a full Fisher effect from 1961:1-2009:4. This result indicates that nominal interest rates do not respond one-for-one to changes in inflation rates in the long run despite the presence of positive relationship among the variables. Our study recommends the adoption of potent policies aimed at checking inflation so as to help reduce high interest rates in order to stimulate growth in the economy.
Keywords: C32; E31; E43; E58; 330; Fisher Effect; Kalman Filter; Inflation; Interest rates; Structural breaks; Cointegration